IP3_Amarelo: Cybernatural and coexistence between nature and machine - Cabral Reis, Artur (DAT Journal, 2021)
This article discusses the theoretical and practical investigation for the development of the emerging and self-organized computational work IP3_AMA¬RELO, exposing the thoughts and concepts which inspired its conception. The text also presents reflections based on the concept of cybernatural proposed by Mitch¬ell Whitelaw, which proposes to explain the possibility of a coexistence between the machinery and the biological, considering the dyad nature-artifice.